Pre-exercise carbohydrate status influences carbohydrate-mediated attenuation of post-exercise Cytokine responses - Cox, A. J.; Pyne, D. B.; Cox, G. R.; Callister, R.; Gleeson, M. (International Journal of Sports Medicine, 2008)
Most studies investigating the effects of acute carbohydrate (CHO) ingestion on post-exercise cytokine responses have involved fasted athletes. This study characterised the effects of acute CHO beverage ingestion preceded by consumption of a CHO-containing pre-exercise meal. Sixteen highly-trained male cyclists/triathletes (age: 30.6 ± 5.6 y; VO2max: 64.8 ± 4.7 ml · kg · min-1 [mean ± SD]) undertook two cycle ergometry trials involving randomised consumption of a 10 % CHO beverage (15 mL· kg-1 · hr-1) or water (H2O). Trials were undertaken 2 h after a breakfast providing 2.1 g CHO · kg-1 body mass (BM) (48 kJ · kg-1 BM) and consisted of 100 min steady state cycle ergometry at 70 % V?O2max followed by a time trial of ~ 30 min duration. Blood samples were collected pre-, post- and 1 h post-exercise for measurement of Interleukin (IL)-6, IL-8, IL-10 and IL-1ra. Time-trial performance was not substantially different between CHO and H2O trials (4.5 %, p = 0.42). Neither IL-6 nor IL-8 responses were substantially reduced in the CHO compared to the H2O trial. There was a substantial reduction in IL-10 (32 %, p = 0.05) and IL-1ra (43 %, p = 0.02) responses at 1 h post-exercise with CHO compared to H2O ingestion. In conclusion, the previously shown attenuating effects of CHO ingestion during exercise on cytokine responses appear reduced when athletes consume a CHO-containing pre-exercise meal.